A1.15 Apolipoprotein E aggravates inflammation and bone destruction in murine antigen – induced arthritis. (24th February 2016) - Ascone, G; Di Ceglie, I; de Munter, W; Walgreen, B; Sloetjes, A; van Lent, P
Abstract : Background and objectives: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterised by severe bone destruction which has been associated with altered lipid metabolism. Apolipoprotein E (ApoE) is a lipoproteincrucial in lipid metabolism, mainly produced by the liver but also by macrophages. Recently ApoE has been described as an important anti-inflammatory mediator regulating innate immunity and as a regulator of bone turnover. Little is known about the role of ApoE in RA. In the present study we investigated the role of ApoE during antigen-induced arthritis (AIA). Materials and methods: Experimental arthritis (AIA) was induced by injection of 60 µg mBSA into the right knee joint of ApoE -/- and wild type (WT) control mice previously immunised with mBSA/CFA. Joint swelling was measured by uptake of 99m Technecium ( 99m Tc) and expressed as a ratio of the uptake in right (injected) knee joint and the left (non injected). Humoral immunity (mBSA antibody titer) was measured by ELISA. Joint inflammation and bone erosion were measured by histological analysis using an arbitrary scale from 0 to 3. TRAP + cells were determined using immunohistochemistry by counting the number of cells along the bone surface. Results: ApoE -/- mice showed significantly less joint swelling at day 1, 3 and 7 after AIA induction compared to WT controls (21%, 17%, 18% lower, respectively). Serum level of specific anti mBSA (total IgG, IgG1, IgG2a and IgG2b) was comparable between the two mouse strains. At day 21 histology of the knee joints showed less infiltration of inflammatory cells (25% lower) and decreased bone erosion in the ApoE -/- mice compared to WT controls (25% lower from 1.5 ± 0.2 to 1.1 ± 0.1. In line with that, in the ApoE -/- mice we found a reduction of the number of osteoclasts present at the area of resorption (36% lower from 20 ± 4 osteoclasts/section in WT mice to 12 ± 5 in ApoE -/- mice), measured by image analysis of TRAP staining. Conclusions: ApoE aggravates bone destruction in AIA by increasing the influx of inflammatory cells within the synovium and the number of resorbing osteoclasts on the bone surface.